Little engines can do big things - Allcroft, Britt; Awdry, W.; Coatimundi Studios (New York : Random House, 2000)
Thomas discovers the magic railroad and the legendary golden engine, Lady.
"Thomas the tank engine & friends ... based on the Railway series by the Rev. W. Awdry."
2.5
K-3
K-3
Keywords: Railroads -- Trains -- Juvenile fiction; Magic -- Juvenile fiction; Railroads -- Trains -- Fiction; Magic -- Fiction; Railroads -- Fiction; Magic -- Fiction